2021
DOI: 10.1002/lno.11994
|View full text |Cite
|
Sign up to set email alerts
|

Examining the influence of regional‐scale variability in temperature and light availability on the depth distribution of subtidal kelp forests

Abstract: Foundation species play a disproportionate role in maintaining biodiversity and ecosystem functioning. Improved understanding of how environmental factors influence the distribution and population structure of foundation species therefore contributes to management and conservation of entire ecosystems. We surveyed subtidal kelp forests within four regions of the U.K., distributed over 9 of latitude and a mean sea temperature gradient of $ 2.5 C. Our aims were: (1) to examine relationships between light availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 65 publications
1
11
0
Order By: Relevance
“…The overlapping light absorption by water column phytoplankton and both green and brown algae action spectra has implications for light harvesting at the seabed and suggests that eutrophication-induced phytoplankton bloom could substantially affect the structure and functioning of benthic macroalgal assemblages, especially at the extremities of light limitation in coastal scenarios (confirming Hypothesis 3). Changes in light availability in terms of quantity, which is usually integrated over the PAR range (400-700 nm), is well known to significantly affect benthic macroalgae assemblages (Airoldi 2003;Clark et al 2013), resilience (Desmond et al 2015;Tait 2019), and their associated ecosystem services like carbon cycles (Blain et al 2021;Smith et al 2021;Weigel and Pfister 2021). However, benthic light also has a spectral quality component, and it is still unclear how changes in spectral light quality tied to changes in OACs in the water column are related to patterns of occurrence in macroalgal communities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overlapping light absorption by water column phytoplankton and both green and brown algae action spectra has implications for light harvesting at the seabed and suggests that eutrophication-induced phytoplankton bloom could substantially affect the structure and functioning of benthic macroalgal assemblages, especially at the extremities of light limitation in coastal scenarios (confirming Hypothesis 3). Changes in light availability in terms of quantity, which is usually integrated over the PAR range (400-700 nm), is well known to significantly affect benthic macroalgae assemblages (Airoldi 2003;Clark et al 2013), resilience (Desmond et al 2015;Tait 2019), and their associated ecosystem services like carbon cycles (Blain et al 2021;Smith et al 2021;Weigel and Pfister 2021). However, benthic light also has a spectral quality component, and it is still unclear how changes in spectral light quality tied to changes in OACs in the water column are related to patterns of occurrence in macroalgal communities.…”
Section: Discussionmentioning
confidence: 99%
“…Most macroalgal assemblages exist in optically complex coastal waters (Gattuso et al 2020; Duarte et al 2022), where a range of land and ocean‐derived organic and inorganic matter alter the absorption and backscatter of light and hence the spectral attenuation of light with depth. It is well known that a shifting light climate has the potential to greatly influence competitive dynamics of macroalgal assemblages with significant implications for net primary productivity, standing biomass, and rates of carbon sequestration (Clark et al 2013; Desmond et al 2015; Tait and Schiel 2018; Tait 2019; Blain et al 2021; Smith et al 2021; Weigel and Pfister 2021). For example, some coastal zones of New Zealand (NZ) experience high levels of sediment runoff (Schiel and Howard‐Williams 2016), and these are associated with detrimental impacts to benthic macroalgal communities (Alestra et al 2014; Tait 2019; Blain et al 2020; Tait et al 2021).…”
mentioning
confidence: 99%
“…For example, M. brachydactyla individuals undertake long-distance migrations into deeper waters on reaching sexual maturity (Corgos et al, 2006), whilst mass recruitment and mortality events of crabs and lobsters have been associated with extreme environmental conditions (e.g. marine heatwaves, see Smith et al, 2021b), both of which contribute to pronounced temporal variability in crustacean population density and size structure. Moreover, decapod crustaceans often exhibit nocturnal or crepuscular peaks in foraging activity (Ennis, 1984;Davenport et al, 2021) and would have been underrepresented in our daytime sampling.…”
Section: Discussionmentioning
confidence: 99%
“…Nutrients were not measured but the study area within the NE Atlantic is not characterized by major upwelling regimes, and previous snapshot sampling at our study sites and longer time series within the regions shows that nutrient concentrations are comparable across this gradient with no difference in key nutrient concentrations between our study sites (Pessarrodona et al ., 2018; Smale et al ., 2020 b ). Previous work at these study sites has shown that they are characterized by extensive kelp canopies dominated by L. hyperborea (Smale et al ., 2016; Smale & Moore, 2017), which extend from the subtidal fringe to depths of ~20 m (Smith et al ., 2021 a ), and support rich and abundant assemblages of associated invertebrates and macroalgae (Teagle et al ., 2018; Bué et al ., 2020; Smale et al ., 2020 a ; King et al ., 2021).
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…However, marine forests are shrinking globally 17,18 due to several impacts such as urbanisation, marine farming, local pollution and herbivory 11,19,20 ; making these habitats more sensitive to global change 5,21 . The structure and productivity of marine forests are influenced by many environmental factors that drive the growth, survival, reproduction and metabolism of the organisms, which in turn affect the whole habitat or ecosystem [22][23][24] . Global change effects on marine forests can vary according to the location, the population characteristics and the species 20,25,26 .…”
mentioning
confidence: 99%